Accessibility of the pores in highly porous alumina films synthesized via sequential infiltration synthesis. (5th October 2018) - She, Yunlong; Lee, Jihyung; Diroll, Benjamin T; Scharf, Thomas W; Shevchenko, Elena V; Berman, Diana
Abstract: Inorganic nanoporous materials with highly accessible pores are of great interest for the design of efficient catalytic, purification and detection systems. Limited access to the pores is a common problem associated with traditional approaches for the synthesis of porous materials, affecting the functionality of the low-density structure. Recently, infiltration of a nanoporous polymer template with inorganic precursors followed by oxidative annealing was proposed as a new and efficient approach to creating porous inorganic structures with controlled thickness, composition and pore sizes. Here, we report an ultra-high accessibility of the pores in porous films prepared via polymer-swelling-assisted sequential infiltration synthesis (SIS). Using a quartz crystal microbalance technique, we show the increased solvent adsorbing capabilities of highly porous alumina films as a result of high interconnectivity of the pores in such structures. The directionality and highly interconnected nature of the pores are demonstrated in experiments with the partial blocking of pore access by the deposition of a single-layer graphene that is not transparent to solvent. 60% of the pores remain accessible when only 20% of the surface is exposed to solvent. Using humidity detection as an example, we also show that highly porous alumina produced by polymer-swelling-assisted SIS is a promising candidate for sensing applications.